Students’ Perception of English Pronunciation Application in Pronouncing Ending –s - Vina Fathira; Diana Zuriati (Lectura : Jurnal Pendidikan, 2021)
Using English Pronunciation in understanding ending –s is one technique to increase the students’ competence, focusing in pronunciation, like in pronouncing ending –s. In digital era, using English Pronunciation in understanding ending –s is the common technique since the students are actively getting involved in gadget. The researchers need in evaluating students’ perception on using English Pronunciation in understanding pronunciation of ending –s. The aim of this research is to investigate students’ perception about the use of English Pronunciation in understanding ending –s. The method employed in this research was qualitative, and it was explained descriptively. The third year semester students at STBA Persada Bunda that used this English Pronunciation application in understanding ending –s were the population as well as the sample of this research. There were 10 students of STBA Persada Bunda in academic year 2018/2019 involved in this study. To collect the data, all students were asked before using English Pronunciation in understanding ending –s from online application and offline one. Then, the researchers distributed six questions related to the students’ perception of using English Pronunciation in understanding ending –s by using interview with semi structured model. The result showed that, most of the third year students were pushed to use English Pronunciation in understanding ending –s in obtaining knowledge and joyful while learning process about voiced sounds, voiceless sound, and sibilant sound. In conclusion, the research about students perception is positive response by using English Pronunciation of pronouncing ending –s.